The possible role of CO2 in producing a post-stimulus CBF and BOLD undershoot - Yucel, Meryem A.; Devor, Anna; Akin, Ata; Boas, David (Frontiers in Neuroenergetics, 2009)
Comprehending the underlying mechanisms of neurovascular coupling is important for understanding the pathogenesis of neurodegenerative diseases related to uncoupling. Moreover, it elucidates the casual relation between the neural signaling and the hemodynamic responses measured with various imaging modalities such as functional magnetic resonance imaging (fMRI). There are mainly two hypotheses concerning this mechanism: a metabolic hypothesis and a neurogenic hypothesis. We have modified recent models of neurovascular coupling adding the effects of both NO (nitric oxide) kinetics, which is a well-known neurogenic vasodilator, and CO2 kinetics as a metabolic vasodilator. We have also added the Hodgkin-Huxley equations relating the membrane potentials to sodium influx through the membrane. Our results show that the dominant factor in the hemodynamic response is NO, however CO2 is important in producing a brief post-stimulus undershoot in the blood flow response that in turn modifies the fMRI BOLD post-stimulus undershoot. Our results suggest that increased cerebral blood flow during stimulation causes CO2 washout which then results in a post-stimulus hypocapnia induced vasoconstrictive effect.